Analisis Antrian pada SS Freis Chicken untuk Menentukan Pelayanan yang Optimal - Harahap, Ainun; Munthe , Alfia Egi Prastia Br; Pane, Dinda Nurinayah (Indo-MathEdu Intellectuals Journal, 2024)
This study was conducted to determine the optimal service with the theory of multi-channel-single phase queues, which is anytime two or more are flowed by a single queue. The research method is a single channel multi-phase method. The variables seen are level of utility, probability, average amount, time. The data used for queuing system analysis is the average number of arrivals per hour and the average number of services per hour. Data collection was based on direct observation at SSFC. The results of this study showed that SS Freis Chicken had to increase its chicken stock. So that the service at SSFC is optimal for customers. Queuing is an unavoidable phenomenon today, manufacturing and service companies are required to be able to reduce queues in providing services to customers. The addition of cashiers is carried out in phase 1, namely the payment stage to 2 people so that it can reduce the average customer waiting in the queue which was originally 10 queues to 0 queues and reduce the average time of customers waiting in the queue which was originally 19.33 minutes / person to 1,002 minutes / person. The addition of cashiers can make the performance of the queuing system more optimal.